Hemostasis at various stages of chronic pulmonary heart development - A. I. Chesnikova (Кардиоваскулярная терапия и профилактика, 2006)
Aim. To study hemostasis and blood rheology in patients with chronic obstructive pulmonary disease (COPD), during chronic pulmonary heart (CPH) development and heart failure (HF) progression. Material and methods. In total, 54 COPD patients (mean age 56.3±8.2 years) were examined: Group I – 17 COPD patients without CPH; Group II - 17 COPD patients with compensated CPH; Group III – 20 COPD patients with CHD and chronic HF (CHF). Control group consisted of 16 healthy volunteers. Vascular-platelet hemostasis parameters: platelet number, spontaneous platelet aggregation, induced aggregation activity and disaggregation potential; plasma hemostasis: coagulation, anticoagulation, and fibrinolysis components; blood rheology: hematocrit, free red cell sedimentation, red cell aggregation - were measured. Results. In COPD patients, moderately decompensated chronic syndrome of disseminated intravascular coagulation (DIC syndrome), leading to microcirculation pathology, was observed. In CPH pathogenesis, microthrombogenesis progression, pulmonary microcirculation abnormalities, pulmonary hypertension progression play an important role. In patients with COPD and CPH, hemostasis was characterized by decompensated DIC syndrome. Compensatory potential of secondary fibrinolysis was substantially decreased at local, organ level. Conclusion. The study demonstrated a leading role of hemostasis in CPH pathogenesis and CHF progression among COPD patients. Disbalance between microthrombosis and secondary organ fibrinolysis could be regarded as CHF marker in COPD individuals.